Management of Cervico-Vaginal and Rectal Prolapse in a Niang Megha Sow under Farm Conditions: A Case Report - Chakravarty, Himsikha; Abedin, Sayed Nabil; Khargaria, G.; Kadirvel, G.; Singh, Mahak; Rautela, Rupali; Deori, Sourabh; Katiyar, Rahul (The Indian Journal of Animal Reproduction, 2022)
The present study deals with a case of cervico-vaginal and rectal prolapse, and its management in a Niang Megha sow. Treatment was carried out using potassium permanganate for washing, turpentine oil, local anaesthetics, antibiotics, analgesic and antihistaminics following repositioning of the prolapsed organs. A significant and uneventful recovery was observed.